Overexpression of CISD2 alleviates septic acute kidney injury via activating Sonic Hedgehog signaling pathway: Effect of CISD2 in septic acute kidney injury - Wu, Wenjun; Zhang, Jia; Chen, Fei; Song, Hongzhuan; Zhou, Xiujie (Cellular and Molecular Biology, 2024)
Patients with sepsis are often complicated by acute kidney injury (AKI), which greatly increases mortality. In this study, our purpose was to explore the expression and function of CDGSH iron sulfur domain 2 (CISD2) in septic AKI, and the underlying molecular mechanism. Western blot and quantitative real-time polymerase chain reaction (RT-PCR) were employed to detect protein and mRNA levels in cells. The inflammation level of cells was evaluated by detecting the content of inflammatory factors (TNF-α, IL-1β, IL-6). Apoptosis of cells was evaluated by Caspase-3 activity assay, flow cytometry and terminal deoxynucleotidyl transferase-mediated dUTP Nick-End Labeling (TUNEL) staining. CISD2 was down-regulated in HK-2 cells treated with lipopolysaccharide (LPS). LPS treatment increased the level of inflammatory factors, the activity of Caspase-3, and the rate of apoptosis in HK-2 cells. However, overexpression of CISD2 significantly suppressed these effects. Moreover, overexpression of CISD2 activated the Sonic Hedgehog (SHH) signaling pathway. The use of cyclopamine (Cyc), a SHH signaling pathway inhibitor, eliminated the effect of overexpressing CISD2, that is, inhibiting LPS-induced inflammation and apoptosis of HK-2 cells. LPS treatment down-regulated CISD2 in HK-2 cells, and overexpression of CISD2 could inhibit LPS-induced inflammation and apoptosis of HK-2 cells by activating the SHH signaling pathway.